The Virtual Coach: Examining the Impact of Perceived Privacy, Anthropomorphism, and Empathy on Overall Well-being in Fitness App Users - Joshi, Surendra Prasad; Ghimire, Binod; Dahal, Rewan Kumar (KMC Research Journal, 2024)
Fitness applications can potentially revolutionize personal well-being in the digital age by fusing empathy, privacy, and human-like engagement. The growing popularity of fitness applications that provide virtual coaching gives a singular chance to study how empathy, anthropomorphism, and perceived privacy affect users' general well-being. With an emphasis on the social and psychological components of virtual connections, this research strives to examine how these characteristics affect the well-being of young people who actively use fitness applications. This study used a positivist paradigm and a descriptive-causal research design. It used primary data questionnaire methods to collect the perspectives of 384 youth actively involved in fitness apps and fitness centers. The findings show that perceived empathy, anthropomorphism, and privacy significantly influence the overall well-being of youths, with empathy being the most effective predictor, followed by anthropomorphism and confidentiality. The results emphasize the significance of well-planned AI-driven interactions in fitness applications and the possibility for sympathetic, human-like virtual coaches to increase user pleasure and encourage better lives. This research advances digital health knowledge by showing relational and privacy-centered designs' significance in improving user well-being and engagement with fitness technology. Future studies might examine long-term effects and other psychological aspects in more detail, presenting information for creating user-centered, adaptable digital exercise settings.